STUDI IMPLEMENTASI BNN KOTA MOJOKERTO DALAM MENGHADAPI KASUS KEJAHATAN NARKOTIKA PADA TAHUN 2022-2024 - Yudha Utama, Jenny; Sidharta Arisandi, Rachman; Alif Prasetyo, Sang (Universitas Islam Majapahit, Indonesia, 2025)
Regarding narcotics crime, the National Narcotics Agency (BNN) reported 851 cases related to narcotics and illegal drugs (narcotics) in Indonesia in 2022. This number increased by 11.1% compared to the previous year's 766 cases. Meanwhile, the number of suspects in drug cases reached 1,350 last year, a 14.02% increase compared to the 1,184 in 2021. To determine the implementation of narcotics crime eradication efforts in the Mojokerto City BNN's jurisdiction, this study aims to determine how the Mojokerto City BNN's eradication efforts are implemented against narcotics crimes in the Mojokerto City BNN's jurisdiction from 2022 to 2024, and what factors influence the success or failure of this implementation. This study uses a qualitative method, which focuses on natural phenomena or phenomena. The implementation outlined here has some flexibility because when eradication is implemented, there are bound to be loopholes or actions outside established policies. Regarding the resource indicators, human resources are still lacking personnel, and budgeting is still carried out by the implementer's initiative in the investigation and inquiry process. There are several shortcomings and strengths in implementing eradication at the Mojokerto City National Narcotics Agency (BNN). If these shortcomings are not addressed, the implementation process will be problematic or even impossible. In 2022, the Eradication Section of the Mojokerto City BNN implemented the following tasks: Investigation and Prosecution and TAT. There were four cases and six suspects prosecuted in Mojokerto Regency (2 cases) and Jombang Regency (2 cases), with a total of 26.86 grams of methamphetamine seized as evidence in 2022.2023: The Eradication Section of the Mojokerto City National Narcotics Agency (BNN) implemented Investigation and Investigation and TAT (Prosecution and Investigation). There were 6 cases involving 10 suspects processed in Mojokerto City (2 cases), Mojokerto Regency (2 cases), and Jombang Regency (2 cases), with a total of 208.76 grams of methamphetamine seized as evidence in 2023. 2024: The Eradication Section of the Mojokerto City National Narcotics Agency implemented only TAT.